Nonlinear modelling and analysis of repaired and retrofitted shear walls - Cortes Puentes, W. Leonardo (University of Ottawa (Canada), 2009)
With advancements in seismic code provisions, mainly as a response to major earthquakes, important parameters such as ductility and energy dissipation have become central in design, resulting in additional detailing for shear walls and other seismic force resisting systems. Due to the large inventory of existing buildings lacking proper detailing for seismic resistance, cost-effective repair and retrofitting techniques have emerged to mitigate seismic risk and satisfy the requirements of current seismic codes. The finite element method (FEM) has emerged as a complementary analytical tool to investigate and assess various repair and retrofitting techniques. This research provides and validates nonlinear modelling procedures for the analysis of repaired and/or retrofitted shear walls using the FEM. Practical techniques including replacement of concrete, addition of reinforcing bars, external bonding of steel/FRP sheets and plates, addition of unbonded steel rods and plates with delay mechanisms, local replacement of concrete, and bolting of steel plates were investigated.
Keywords: Engineering, Civil.